Interferensi Bahasa dan Upaya Intervensinya dalam Pengajaran Mahārah Kitābah - Yuslizar, Fairus Afra; Wargadinata, Wildana; Muassomah (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2025)
This study aims to analyze the dynamics of interference and intervention in Arabic writing learning within an Islamic boarding school context. Conducted longitudinally over three years with 24 students at Al-Izzah Integrated Islamic Boarding School (IIBS) in Batu City, this research employed a descriptive qualitative approach under the frameworks of Cultural-Historical Activity Theory (CHAT) and Zone of Proximal Development (ZPD). Data were collected through classroom observations, students’ writing analysis, and in-depth interviews with Arabic teachers. The findings reveal that linguistic interference is not merely a structural error but rather a manifestation of the developmental nature of learners’ interlanguage systems. Pedagogical interventions such as authentic writing tasks, cultural scaffolding, and reflective mentoring were proven effective in reducing syntactic, semantic, and orthographic interference. The study highlights that language learning is a dialectical interaction among linguistic, psychological, and cultural factors. Theoretically, this research reinforces the Dynamic Theory of Interference–Intervention (DTII) as a comprehensive framework for foreign language education, while practically emphasizing the importance of developmental and metalinguistic awareness-based instructional strategies.